Integration of Digital Technologies in Environmental Education: A Systematic Review of Trends, Impacts, and Future Directions - H. Husamah; Abdulkadir Rahardjanto; Tutut Indria Permana; Ahmad Adnan Mohd Shukri (Universitas Muhammadiyah Surakarta, 2025)
The integration of digital technologies in environmental education (EE) has emerged as an important research area. However, a comprehensive synthesis of international research remains scarce. This systematic literature review (SLR), adhering to the PRISMA guidelines, aims to fill this gap by synthesizing peer-reviewed articles published in the past decade, specifically from the Scopus database. While the Scopus database was prioritized due to its comprehensive collection of high-quality, peer-reviewed journals in the field, future research should consider incorporating studies from other databases to ensure broader coverage of the topic. The primary objectives of this review are to analyze: (1) the predominant research approaches and instruments used in digital technology research in EE; (2) key findings regarding the application of digital technologies in EE; (3) thematic categories that explain the role of digital tools in environmental learning; and (4) the impact of digital technologies on promoting pro-environmental behavior through pedagogical integration. This review synthesizes current research practices and outlines how technologies such as augmented reality (AR), virtual reality (VR), and mobile applications enhance student engagement, environmental knowledge, and pro-environmental behavior. Additionally, the review explores the potential risks associated with the adoption of digital technologies, including the phenomenon of